1992
DOI: 10.1152/jappl.1992.73.4.1396
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine immunoreactivity in plasma does not change after moderate endurance exercise

Abstract: We investigated whether increased concentrations of circulating cytokines may be responsible for exercise-induced priming of blood neutrophils (J. A. Smith et al. Int. J. Sports Med. 11: 179-187, 1990). The plasma concentrations of tumor necrosis factor-alpha, interleukin- (IL) 1 beta, IL-6, granulocyte-macrophage colony-stimulating factor, and neopterin in trained and untrained human subjects were measured by immunoassay before and after 1 h of cycling at 60% of maximal oxygen uptake. C-reactive protein and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
2
2

Year Published

1994
1994
2007
2007

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 0 publications
4
25
2
2
Order By: Relevance
“…These results suggest that elevations in CRP following exercise may not be solely due to muscle damage. Supporting this would be the findings of Smith et al 43 In this study, CRP was significantly (p < 0.04) elevated in 75% of active-untrained subjects, 24 hours after performing 60 minutes of cycling at only 60% of maximal oxygen uptake. Similarly, Meyer et al 26 reported a significant (p = 0.02) increase in CRP 24 hours after 12 trained males performed an anaerobic cycle ergometer test.…”
Section: Effects Of Acute Exercise On Crpsupporting
confidence: 78%
“…These results suggest that elevations in CRP following exercise may not be solely due to muscle damage. Supporting this would be the findings of Smith et al 43 In this study, CRP was significantly (p < 0.04) elevated in 75% of active-untrained subjects, 24 hours after performing 60 minutes of cycling at only 60% of maximal oxygen uptake. Similarly, Meyer et al 26 reported a significant (p = 0.02) increase in CRP 24 hours after 12 trained males performed an anaerobic cycle ergometer test.…”
Section: Effects Of Acute Exercise On Crpsupporting
confidence: 78%
“…Moreover, blood levels of TNF and IF are not changed by moderate exercise (Haahr et al 1991;Smith et al 1992;Pedersen et al 1994). In the present study, the plasma levels of IL-1 and TNF were not affected immediately after the marathon race, suggesting that the monocytes and macrophages were not activated by the exercise.…”
Section: Discussionmentioning
confidence: 98%
“…The authors Haralmabie (24), Hanson (25) and Weiss (26) As an important serum marker for the activation of the cellular immune system, neopterin was studied more recently by several other investigators (27)(28)(29)(30)(31)(32). Rokos (27) studied four male subjects aged 31 to 47 before, during and after 100 min of jogging.…”
Section: Discussionmentioning
confidence: 99%